NATIONAL AND CULTURAL REALIA REFLECTED IN ENGLISH PROVERBS (World Bulletin of Education and Learning, 2025)
The article is devoted to the analysis of English proverbs, which express the national and cultural specifics of the people. The promotion of such a meaning in proverbs is carried out through the use of national realias. Realias are words that reflect cultural peculiarities of the people of the world. There are a great deal a realias in any language (realias of clothes, food, drink, holidays, customs etc.). Most importantly, their functioning in proverbs has a linguistic and cultural significance, as they demonstrate cultural values in the history of the people and the state. English proverbs with national realias show the richness of a certain language, national-cultural specifics and historical value of the people. In the course of the work, such methods as the semantic-stylistic, the method of intralingual comparison and the descriptive method were used.
Keywords: Proverb, analysis, national, cultural, English, realia.